ANALYSIS OF ERGONOMIC LIGHTING IN THE ENGINEERING FACULTY WORKSPACE OF MURIA KUDUS UNIVERSITY - akh sokhibi; Mia Ajeng Alifiana; Vikha Indira Asri (Spektrum Industri, 2020)
Lighting is an important factor in working comfort. A comfortable workspace must meet good lighting requirements by the lighting standards of a workplace. Visual comfort at work is the result of applying ergonomic aspects to workspace lighting. The purpose of this research is to analyze ergonomically lighting in the workspace of the engineering faculty of Muria Suci University. The method used in this research is descriptive quantitative. Where the data collection of light measurement in the workspace is carried out at the hour (09.00-14.00 WIB). Then the data is processed using surfer software version 10 to determine the distribution of lighting. Testing is done by comparing the standardization table of lighting intensity levels based on SNI 03-6575-2001 standards. Risk data the visual comfort of the lighting at work is analyzed in terms of the level of lighting risk. The results of this study indicate that quantitative exposure risk, all work spaces of the Faculty of Engineering, Muria Kudus University does not eligible SNI 03-6575-2001. Meanwhile, based on the risk of qualitative lighting, administrative workspaces that have a low risk of visual comfort and industrial engineering study program workspaces have a high risk of visual comfort